Effects of combined upper and lower limb plyometric training interventions on physical fitness in athletes: a systematic review with meta-analysis - Deng, Nuannuan; Soh, Kim Geok; Zaremohzzabieh, Zeinab; Abdullah, Borhannudin; Md Salleh, Kamariah; Huang, Dandan (Multidisciplinary Digital Publishing Institute, 2022)
Objective: We aimed to meta-analyze the effects of combined upper and lower limb plyometric training (ULLPT) on physical fitness attributes in athletes. Methods: A systematic literature search was conducted in Web of Science, SPORTDiscus, PubMed, and SCOPUS, for up to 13 August 2022. Controlled studies with baseline and follow-up measures were included if they examined the effects of ULLPT on at least one measure of physical fitness indices in athletes. A random effects meta-analysis was performed using the Comprehensive Meta-Analysis software. Results: Fifteen moderate-to-high-quality studies with 523 participants aged 12–22.4 years were included in the analyses. Small to large (ES = 0.42–1.66; p = 0.004 to <0.001) effects were noted for upper and lower body muscle power, linear sprint speed, upper and lower body muscle strength, agility, and flexibility, while no significant effects on static and dynamic balance were noted (ES = 0.44–0.10; all p > 0.05). Athletes’ sex, age, and training program variables had no modulator role on the effects of ULLPT in available data sets. Conclusions: ULLPT induces distinct neuro-muscular adaptations in the upper and lower body musculature and is an efficient method for enhancing athletes’ physical fitness.